Display surface protection film with antifouling and antistatic functions and preparation method thereof

By introducing an antistatic layer, an antifouling layer and an adhesive layer into the surface protective film, the problem of increased oligomer adhesion and peeling force in the prior art is solved, and the surface protection effect of high transparency, antifouling and anti-static is achieved, reducing production costs and improving product quality.

CN119592243AInactive Publication Date: 2025-03-11Shenzhen Xinjingke Optoelectronic Equipment Co., Ltd.
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411788043.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing surface protective film produces oligomer adhesion in the heat treatment process, resulting in contamination and operation difficulties, and the peeling force increases, affecting product quality.

Method used

A polyester film with anti-fouling and anti-static functions is used as the surface protective film. By providing an anti-static layer, anti-fouling layer and an adhesive layer on the film, the laminated structure is not contaminated and good peeling properties are maintained at high temperatures.

Benefits of technology

It effectively reduces the problems of oligomer adhesion and pollution, improves the heat resistance and peelability of the surface protective film, reduces production costs, and improves product yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592243A_ABST
    Figure CN119592243A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of display screen control panels, and discloses a display surface protection film with antifouling and antistatic functions and a preparation method thereof, the average roughness Ra of the center line of a polyester film is preferably 2-500nm, the number of foreign matters with the average diameter of more than 25 microns is preferably 0 for the region of 210mm of the edge on the polyester film and 148mm of the edge directly connected with the edge, and the number of the foreign matters with the average diameter of more than 25 microns is preferably 0 for the region of 210mm of the edge on the polyester film and 148mm of the edge directly connected with the edge on the polyester film. It is preferable that the number of foreign matters having an average diameter of 5 [mu] m or more and less than 25 [mu] m is 10 or less. The surface protective film uses an antistatic film as a base material. According to the invention, as a polyethylene glycol terephthalate film, a polyethylene glycol terephthalate polymer containing 0.1% by weight of true spherical silicon dioxide particles with an average particle size of 0.15 [mu] m and an intrinsic viscosity of 0.62 is melted in an extruder, and is tightly adhered to a rotary cooling drum with a distance of 40 DEG C from a mold by using an electrostatic close method; and quickly cooling to form an unstretched film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a display control panel, which is widely used in the field of surface protection film production technology in the manufacturing process of various soft and hard displays such as liquid crystal televisions, flexible notebooks, flexible display screens, flexible mobile phones, word processors, and car navigation systems. The invention relates to a display surface protection film with high transparency polyester film having anti-fouling and anti-static functions and a preparation method thereof. Background Art

[0002] The existing surface protection film generally has a plastic film as the base material, and a structure with an adhesive layer on one side of the film. In recent years, its use as the surface protection of optical components has been expanding. It includes the surface protection of various displays used in the manufacture of televisions, computers, word processors, and car navigation. Among them, the surface protection of liquid crystal display panels, i.e. LCDs, and the surface protection of optical components such as polarizing plates, phase difference plates, and viewing angle magnification films in the manufacturing process are growing rapidly. Optical laminates and optical laminates.

[0003] In general, as the surface protection film substrate, polyethylene or polypropylene transparent materials are used, and olefin-based films are used. After the manufacture and assembly of liquid crystal displays, etc. are completed or in actual use, these surface protection films are peeled off and removed. TFT technology occupies a core position in the flat panel display industry, and is characterized by capital intensiveness, talent intensiveness, and technology intensiveness. The panel output value is high and the industrial agglomeration effect is obvious. Although TFT technology is mature and still developing rapidly, there is still room to continuously reduce production costs by improving film materials and preparation processes, while improving panel performance. In recent years, TFT-based liquid crystal displays have received special attention due to their high fineness and high responsiveness, and the requirements for surface protection films in their manufacturing process are becoming more and more stringent. Including, in the manufacturing process of TFT-based liquid crystal displays, a heat treatment process of about 140°C or the use of a polyester film with excellent heat resistance.

[0004] However, the surface protective film produces oligomers during the drying and heating process in the tube manufacturing process and during the heat treatment process in the liquid crystal display manufacturing process, which adhere to the process rollers in the polarizing plate manufacturing process, contaminating the product, or unevenly inspecting the product defects when manufacturing the optical plate or liquid crystal display with the surface protective film attached. During the inspection, the surface becomes blurred and foggy due to the production of oligomers, and the inspection operability deteriorates. In addition, once the surface protective film is attached to the polarizing plate or liquid crystal display, it is usually attached for a long time before the next manufacturing process. Then, after the inspection is completed, the peeling force becomes high at this time, the operation deteriorates, or a part of the film adhesive remains, and the display inspection of the display produces foreign matter and deformation defects. For this reason, the present invention designs a display surface protective film with anti-fouling and anti-static functions and a preparation method thereof. Summary of the invention

[0005] The present invention aims to solve the above-mentioned problems of the prior art and provide a low polymer which is produced in small amounts even after heat treatment and is easy to peel off after being attached to the substrate of the product and has a peeling force that does not change after being durable, thereby reducing costs and improving product yields. It also has the functions of a surface protective film with high transparency, anti-fouling and anti-static properties. The present invention provides a surface protective film and a laminate thereof that do not damage the inspection properties of the substrate of the product to be attached.

[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a display surface protection film with antifouling and antistatic functions, comprising a polyester film, wherein the center line average roughness of the polyester film, i.e., Ra, is preferably 2-500nm, and for the area of ​​the edge 210mm and the edge 148mm directly therefrom on the polyester film, the number of foreign matters with an average diameter of 25μm or more is preferably 0, and the number of foreign matters with an average diameter of 5μm or more and less than 25μm is preferably 10 or less; the surface protection film uses an antistatic film as a substrate, and the antistatic film is formed on the polyester film. A layer containing an antistatic agent is provided on at least one surface, and a thermoplastic resin of a thermoplastic polyester resin and an acrylic resin is used as an adhesive; an antifouling layer is provided on one surface of the antistatic film, and the antifouling layer adopts a formula of an adhesive and an antifouling agent, and the antifouling agent accounts for 3 to 25% by weight of the antifouling layer. As the antifouling agent, an alkyl polymer-type release agent with particularly low migration is preferred from the perspective of preventing contamination during the process, and as the adhesive, a thermosetting resin is used as an adhesive for the antifouling layer; the polyester film protective film includes an adhesive layer on the antistatic film, and the adhesive layer is provided on the antistatic film. On the surface opposite to the surface of the antifouling layer, the antifouling layer and the adhesive layer are located on the opposite side of the clamping antistatic film; the adhesive layer is provided to paste and fix the surface protection to the relative substrate, the adhesive layer is made of an adhesive, and is an acrylic adhesive; the thickness of the adhesive layer is 5 to 50um, and the normal adhesion of the adhesive layer to the stainless steel plate is 3g / 25mm to 50g / 25mm. The adhesive layer should be adhered to the stainless steel plate at 60°C, and the normal adhesion change rate is preferably 0.5 to 2.0 times before and after one week. The adhesive can be applied directly to the antistatic film or applied on a release paper. The adhesive is transferred to the release paper with a smooth surface, and the drying temperature and time are set at a temperature of 50 to 150°C, and the drying time is set for 10 seconds to 5 minutes. The surface protective film has a light transmittance of 70% and a haze of 10%. The release paper adopts a laminate structure, in which the release paper is arranged on the adhesive layer to protect the adhesive layer of the surface protective film, and the release paper with a polyester film as the base material is further laminated on the adhesive layer of the surface protective film.

[0007] Preferably, the antistatic layer is doped with a crosslinking agent, and the crosslinking material is methylolated and alkylated melamine compounds, urea compounds, acrylamide compounds, epoxy compounds, and polyisocyanate compounds.

[0008] Preferably, the antistatic agent adopts a surfactant type antistatic agent, a cationic antistatic agent with a cationic substituent group, including a quaternary ammonium salt, a pyridinium salt, and a 1-3 amino group, an anionic antistatic agent with an anionic substituent group, including a sulfonic acid base, a nitrate base, a phosphate base, and an amino acid and aminosulfate amphoteric antistatic agents, amino alcohol, glycerol and polyethylene glycol non-ionic antistatic agents, used as monomers and high molecular polymers, and conductive polymers, including polyaniline, polypyrrole, polythiophene, tin and antimony fillers can also be used. When a polyester film is set, an antistatic layer is set before the crystal orientation is completed during the film formation. In order to set the antistatic layer, the antistatic agent and the adhesive are coated on the polyester film. The coating method adopts a roll coating method, a gravure coating method, a reverse coating method, and a spray coating method; they can be used alone or in combination.

[0009] Preferably, the thickness of the antifouling layer is 0.05 to 0.8um. ​​When the antifouling layer is thinner than 0.02um, it cannot prevent the precipitation of oligomers. When it is thicker than 3um, it is easy to cause blockage. When the antistatic film is set, the antifouling layer is set before the crystal orientation is completed during film formation. In order to set the antifouling layer, the antifouling agent and adhesive are usually coated on the antistatic film. The coating method adopts roller coating, gravure coating, reverse coating, and spray coating, which can be used alone or in combination.

[0010] Preferably, the adhesive has good adhesion, the size of the ball in the ball adhesion measurement is preferably 2 / 32 to 10 / 32 inches, and after the surface protection film is adhered to the other substrate, it needs to be peeled off in the next manufacturing assembly process and the last process. The center line average roughness of the adhesive layer, i.e., Ra, is preferably 2 to 500nm. The center line average roughness of the adhesive layer is measured by scanning the surface of the laminated film using a non-contact three-dimensional surface roughness meter to measure the displacement of the film surface, and the center surface average roughness, i.e., Ra, is obtained through surface analysis software. The acrylic adhesive used is preferably the following adhesive.

[0011] Preferably, a polyester film is used as the substrate of the release paper. The polyester film has the same structure as the polyester film of the surface protection film. The polyester film of the release paper is preferably a biaxially stretched polyester film. Preferably, a release layer is formed on one surface of the release paper.

[0012] Preferably, the components forming the release paper are mixed with various well-known additives, including ultraviolet absorber pigments, defoamers, and antistatic agents. The release layer is applied by applying a coating liquid containing the components forming the separation layer to the base film and heating and drying to form a coating film. The heating conditions are 120-150° C. for 20-60 seconds, and the coating methods include a roll coater method and a comma coater method.

[0013] Preferably, an adhesive layer is provided between the base film and the release layer, and as a component forming the adhesive layer, when the release layer is a silicone resin layer, a silane coupling agent is preferred.

[0014] Preferably, the silane coupling agent is more preferably represented by the general formula Y-Si-X 3, Y represents a functional group represented by amino, epoxy, vinyl, methacrylate, and mercapto, X represents a hydrolyzable functional group represented by alkoxy, and the thickness of the adhesive layer is in the range of 0.02 to 2 um.

[0015] A method for preparing a display surface protective film with antifouling and antistatic functions comprises the following steps:

[0016] Step S1, an antistatic layer is provided on the polyester film. On the antistatic film, an anti-seepage layer and an adhesive layer are provided as a surface protective film, in which the non-polluting anti-slip layer and the adhesive layer are located on the opposite side of the antistatic film. After the surface protective film is placed at 140° C. for 10 minutes, the surface of the anti-fouling layer satisfies the following conditions:

[0017] Step S2, in a square area with a side of 40 μm, the surface protection film is an antistatic film in which an antistatic layer is arranged on a polyester film, and an antifouling layer and an adhesive layer are arranged on the pipe. In the antistatic film, the antistatic layer is arranged on one side of the polyester film, and can also be arranged on both sides;

[0018] Step S3, the antifouling layer and the adhesive layer are located on the opposite side of the clamped antistatic film, the surface protective film, for the surface of the antifouling layer after being placed at 140°C for 10 minutes, in the square area with a side of 40μm, there are only five low-sided contamination levels with a diameter of 0.5μm or more in the maximum length direction. If more than 5 exist, the surface of the metal roller in the process, the polyester film is used as the substrate of the antistatic film of the surface protective film substrate, and the use of the polyester film can be manufactured by the existing known manufacturing method, preferably the biaxially oriented polyester film is the first choice, as the biaxially oriented polyester film , biaxially oriented polyethylene terephthalate films and biaxially oriented polyethylene-2,6-phthalate films can be used, and these films can be single-layer films or multi-layer films in their structure. In the case of multi-layer films, a multi-layer structure with any number of layers can be formed by coextrusion. The polyester constituting the polyester film is preferably a crystalline linear saturated polyester composed of an aromatic dibasic acid component and a diol component, including polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate and polyethylene-2,6-naphthalene dicarboxylate;

[0019] Step S4, in addition, a part of which is a copolymer substituted by other components, can also be a mixture with polyalkylene glycol or other resins; when the biaxially oriented polyester film is used as the polyester film, the biaxially oriented polyester film can be manufactured by methods such as sequential biaxial stretching method and simultaneous biaxial stretching method;

[0020] Step S5, when the sequential biaxial stretching method is adopted, the following method is adopted: after the polyester polymer is fully dried, it is extruded from the tube core, including the T-tube core and the I-tube core, onto a cooling drum by melt extrusion, and quenched to obtain an unstretched film and a co-extruded unstretched film, and then the unstretched film is longitudinally stretched 2 to 5 times at a temperature of 60 to 140° C., and then transversely stretched 2 to 5 times at a temperature of 80 to 150° C., and then heat-fixed at a temperature of 160 to 260° C. for 1 to 100 seconds, and the heat-fixing treatment is performed under the condition of limiting shrinkage;

[0021] Step S6. During melt extrusion, an electrostatic bonding method is used. In addition, in order to avoid breakage in a specific direction, the isotropy of the biaxially oriented polyester film is preferably as high as possible, including the above-mentioned longitudinal and transverse stretching ratios are preferably the same, and the thickness of the film is preferably 5 to 50 μm, more preferably 10 to 200 μm.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. An antistatic layer is set on the polyester film. On the antistatic film, an anti-seepage layer and an adhesive layer are set on the surface protective film. In the surface protective film, the non-polluting anti-slip layer and the adhesive layer are located on the opposite side of the antistatic film. After the surface protective film is placed at 140°C for 10 minutes, the surface of the antifouling layer meets the following conditions: surface protective film; in a square area of ​​40μm on one side, the diameter in the maximum length direction is 0.5μm or more. There are only 5 types of oligomer pollution at most. The surface protective film is an antistatic film with an antistatic layer on the polyester film. The antifouling layer and the adhesive layer are set on the pipe. In the antistatic film, the antistatic layer is set on one side of the polyester film, and can also be set on both sides.

[0024] 2. In the present invention, the anti-fouling layer and the adhesive layer are located on the opposite side of the clamped antistatic film, and the surface protective film has only five degrees of low-sided contamination with a diameter of more than 0.5 μm in the maximum length direction in the 40 μm square area. If more than 5 exist, the surface of the metal roller in the process, especially the oligomers attached to the surface of the clamped metal roller, becomes obvious, deteriorates the flatness of the product, and avoids the oligomers deposited on the metal roller from being re-transferred to the product. The contamination is easily pulled. The polyester film is used as the substrate of the antistatic film of the surface protection film substrate, and has high transparency. From the viewpoint of obtaining a high surface protection film, the polyester film is used. The polyester film can be manufactured by an existing known manufacturing method. From the perspective of heat resistance, productivity and processability of the polyester film, a biaxially oriented polyester film is preferably the first choice. As the biaxially oriented polyester film, a biaxially oriented polyethylene terephthalate film or a biaxially oriented polyethylene-2,6-phthalate film can be used. These films can be single-layer films or multi-layer films in their structure. In the case of a multi-layer film, by co- A multilayer structure having any number of layers can be formed by extrusion. The polyester constituting the polyester film is preferably a crystalline linear saturated polyester composed of an aromatic dibasic acid component and a diol component, including polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate and polyethylene-2,6-naphthalene dicarboxylate; in addition, a part of them is a copolymer substituted by other components, and it can also be a mixture with polyalkylene glycol or other resins; when a biaxially oriented polyester film is used as the polyester film, the biaxially oriented polyester film can be manufactured by methods such as sequential biaxial stretching method and simultaneous biaxial stretching method.

[0025] 3. When the sequential biaxial stretching method is used, the following method is used: after the polyester polymer is fully dried, it is extruded from a tube core, including a T-tube core and an I-tube core, onto a cooling drum by melt extrusion, and quenched to obtain an unstretched film and a co-extruded unstretched film, and then the unstretched film is longitudinally stretched 2 to 5 times at a temperature of 60 to 140°C, and then transversely stretched 2 to 5 times at a temperature of 80 to 150°C, and then heat-fixed at a temperature of 160 to 260°C for 1 to 100 seconds to obtain the film, and the heat-fixing treatment is performed under limited shrinkage. In addition, during melt extrusion, an electrostatic bonding method is used. In addition, even in order to prevent breakage in a specific direction, the isotropy of the biaxially oriented polyester film is preferably as high as possible, including the longitudinal and The transverse stretching ratio is preferably the same, and the thickness of the film is preferably 5 to 50 μm, more preferably 10 to 200 μm, to improve the processability and productivity of pasting. In order to have good slippage when rolling the film, and good handling performance during processing such as adhesive coating, the polyester film can contain a lubricant, including inorganic particles of calcium carbonate, aluminum oxide, kaolin, silica, titanium oxide, barium sulfate, zeolite, organic particles such as silicone resin, cross-linked polystyrene, acrylic resin, and other additives, including stabilizers, ultraviolet absorbers, flame retardants and antistatic agents. The time for adding the particles and additives is preferably before the polyester film is formed, including addition in the polymerization stage, and can also be added during film formation. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a diagram showing the evaluation results of the protective film proposed in the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The present invention provides a display surface protection film with antifouling and antistatic functions and a preparation method thereof, comprising a polyester film, wherein the center line average roughness of the polyester film, i.e., Ra, is preferably 2-500 nm, and for the area of ​​the edge 210 mm and the edge 148 mm directly therefrom on the polyester film, the number of foreign matters with an average diameter of 25 μm or more is preferably 0, and the number of foreign matters with an average diameter of 5 μm or more and less than 25 μm is preferably 10 or less; the surface protection film uses an antistatic film as a substrate, and the antistatic film is provided with a layer containing an antistatic agent on at least one surface of the polyester film, so that it can prevent The invention relates to a method for preventing the damage caused by the peeling charge of the TFT arranged on the polarizing plate when the surface protection layer is peeled off, and preventing the friction charge of the polarizing plate laminate with the laminated surface protection film during the assembly process of the liquid crystal display; in order to improve the strength of the layer, as well as to improve the adhesion, water resistance, solvent resistance and blocking resistance with the polyester film, it is best to use an antistatic layer in which an antistatic agent is mixed in the adhesive; as the adhesive, a thermoplastic resin of a thermoplastic polyester resin and an acrylic resin is used; an antifouling layer is provided on one surface of the antistatic film, and the antifouling layer adopts a formula of an adhesive and an antifouling agent, and the proportion of the antifouling agent in the antifouling layer is 3 to 25%. weight, if less than 1% by weight, sufficient antifouling property cannot be exhibited; if more than 40% by weight, the compactness of the antifouling layer becomes poor and the precipitation of oligomers cannot be prevented; the purpose of the antifouling agent is to prevent the contamination of the surface of the surface protection film, so it is preferably to have a moderate peeling force and be durable, and as the antifouling agent, an alkyl polymer-based release agent with particularly low migration is preferred from the perspective of preventing contamination during the process, and as an adhesive, a thermosetting resin is used as an adhesive for the antifouling layer; the polyester film protective film includes an adhesive layer on the antistatic film, the adhesive layer is provided on the surface opposite to the surface provided with the antifouling layer, and the antifouling layer and the adhesive layer are Located on the opposite side of the clamped antistatic film; an adhesive layer is provided to paste and fix the surface protection to the opposite substrate, the adhesive layer is made of an adhesive, considering that this self-adhesive is placed not only indoors but also outdoors, and in order to withstand various lights during inspection, it is required to be UV-resistant, and in order to prevent the transfer of components from the self-adhesive layer to the other substrate to be bonded, it is an acrylic self-adhesive; the thickness of the adhesive layer is 5 to 50um, and the normal adhesion of the adhesive layer to the stainless steel plate is 3g / 25mm~50g / 25mm. The adhesive layer should be bonded to the stainless steel plate at 60℃, and the normal adhesion change rate before and after one week is 0.5~2.0 times is appropriate. The adhesive can be applied directly to the antistatic film or applied once on the release paper. After drying, the antistatic films are attached together to transfer the adhesive. Apply once on the release paper with a smooth surface and transfer it to the antistatic film. The drying temperature and time are set at a temperature of 50 to 150°C for 10 seconds to 5 minutes. Heat at room temperature for more than 7 days. The light transmittance of the surface protective film is 70% and the haze is 10%. The release paper adopts a laminate structure, in which the release paper is set on the adhesive layer to protect the adhesive layer of the surface protective film. The release paper with a polyester film as the base material is further laminated on the adhesive layer of the surface protective film. .

[0029] In this embodiment, the antistatic layer is doped with a crosslinking agent, and the crosslinking material adopts hydroxymethylated and alkylated melamine compounds, urea compounds, acrylamide compounds, epoxy compounds, and polyisocyanate compounds;

[0030] In this embodiment, the antistatic agent adopts a surfactant type antistatic agent, a cationic antistatic agent with a cationic substituent group, including a quaternary ammonium salt, a pyridinium salt, and a 1-3 amino group, an anionic antistatic agent with an anionic substituent group, including a sulfonic acid base, a nitrate base, a phosphate base, and an amino acid and aminosulfate amphoteric antistatic agents, amino alcohols, glycerols and polyethylene glycol nonionic antistatic agents, used as monomers and high molecular polymers, and conductive polymers, including polyaniline, polypyrrole, polythiophene, tin and antimony fillers, when a polyester film is set, an antistatic layer is set before the crystal orientation is completed during the film formation period, in order to set the antistatic layer, the antistatic agent and the adhesive are coated on the polyester film, and the coating method adopts a roll coating method, a gravure coating method, a reverse coating method, and a spray coating method; they can be used alone or in combination;

[0031] In this embodiment, the thickness of the anti-fouling layer is 0.05 to 0.8um. ​​When the anti-fouling layer is thinner than 0.02um, it cannot prevent the precipitation of oligomers. When it is thicker than 3um, it is easy to cause blockage. When the anti-static film is set, the anti-fouling layer is set before the crystal orientation is completed during film formation. In order to set the anti-fouling layer, the anti-fouling agent and adhesive are usually coated on the anti-static film. The coating method adopts roller coating, gravure coating, reverse coating, and spray coating. They can be used alone or in combination.

[0032] In this embodiment, the adhesion of the adhesive, the size of the ball in the ball adhesion measurement is preferably 2 / 32 to 10 / 32 inches, and after the surface protection film is adhered to the other substrate, it needs to be peeled off in the next manufacturing assembly process and the last process. The center line average roughness of the adhesive layer, i.e., Ra, is preferably 2 to 500nm. The center line average roughness of the adhesive layer is measured by scanning the surface of the laminated film using a non-contact three-dimensional surface roughness meter to measure the displacement of the film surface. The center surface average roughness, i.e., Ra, is obtained through surface analysis software. The acrylic adhesive used is preferably the following adhesive.

[0033] In this embodiment, a polyester film is used as the substrate of the release paper. The polyester film has the same structure as the polyester film of the surface protection film. The polyester film of the release paper is preferably a biaxially stretched polyester film. Preferably, a release layer is formed on one surface of the release paper.

[0034] In this embodiment, the components forming the release paper are mixed with various well-known additives, including ultraviolet absorber pigments, defoaming agents, and antistatic agents. The release layer is applied by applying a coating liquid containing the components forming the separation layer onto the base film and heating and drying to form a coating film. The heating conditions are 120-150°C for 20-60 seconds, and the coating methods include a roll coater method and a comma coater method.

[0035] In this embodiment, an adhesive layer is provided between the base film and the release layer, and as a component forming the adhesive layer, when the release layer is a silicone resin layer, a silane coupling agent is preferred.

[0036] In this embodiment, the silane coupling agent is more preferably represented by the general formula Y-Si-X 3, where Y represents a functional group represented by an amino group, an epoxy group, a vinyl group, a methacrylate group, or a mercapto group, and X represents a hydrolyzable functional group represented by an alkoxy group. The thickness of the adhesive layer is in the range of 0.02 to 2 um.

[0037] A method for preparing a display surface protective film with antifouling and antistatic functions comprises the following steps:

[0038] Step S1, an antistatic layer is provided on the polyester film. On the antistatic film, an anti-seepage layer and an adhesive layer are provided as a surface protective film, in which the non-polluting anti-slip layer and the adhesive layer are located on the opposite side of the antistatic film. After the surface protective film is placed at 140° C. for 10 minutes, the surface of the anti-fouling layer satisfies the following conditions:

[0039] Step S2, in a square area with a side of 40 μm, the surface protection film is an antistatic film in which an antistatic layer is arranged on a polyester film, and an antifouling layer and an adhesive layer are arranged on the pipe. In the antistatic film, the antistatic layer is arranged on one side of the polyester film, and can also be arranged on both sides;

[0040] Step S3, the antifouling layer and the adhesive layer are located on the opposite side of the clamped antistatic film, the surface protective film, for the surface of the antifouling layer after being placed at 140°C for 10 minutes, in the square area with a side of 40μm, there are only five low-sided contamination levels with a diameter of 0.5μm or more in the maximum length direction. If more than 5 exist, the surface of the metal roller in the process, the polyester film is used as the substrate of the antistatic film of the surface protective film substrate, and the use of the polyester film can be manufactured by the existing known manufacturing method, preferably the biaxially oriented polyester film is the first choice, as the biaxially oriented polyester film , biaxially oriented polyethylene terephthalate films and biaxially oriented polyethylene-2,6-phthalate films can be used, and these films can be single-layer films or multi-layer films in their structure. In the case of multi-layer films, a multi-layer structure with any number of layers can be formed by coextrusion. The polyester constituting the polyester film is preferably a crystalline linear saturated polyester composed of an aromatic dibasic acid component and a diol component, including polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate and polyethylene-2,6-naphthalene dicarboxylate;

[0041] Step S4, in addition, a part of which is a copolymer substituted by other components, can also be a mixture with polyalkylene glycol or other resins; when the biaxially oriented polyester film is used as the polyester film, the biaxially oriented polyester film can be manufactured by methods such as sequential biaxial stretching method and simultaneous biaxial stretching method;

[0042] Step S5, when the sequential biaxial stretching method is adopted, the following method is adopted: after the polyester polymer is fully dried, it is extruded from the tube core, including the T-tube core and the I-tube core, onto a cooling drum by melt extrusion, and quenched to obtain an unstretched film and a co-extruded unstretched film, and then the unstretched film is longitudinally stretched 2 to 5 times at a temperature of 60 to 140° C., and then transversely stretched 2 to 5 times at a temperature of 80 to 150° C., and then heat-fixed at a temperature of 160 to 260° C. for 1 to 100 seconds, and the heat-fixing treatment is performed under the condition of limiting shrinkage;

[0043] Step S6. During melt extrusion, an electrostatic bonding method is used. In addition, in order to avoid breakage in a specific direction, the isotropy of the biaxially oriented polyester film is preferably as high as possible, including the above-mentioned longitudinal and transverse stretching ratios are preferably the same, and the thickness of the film is preferably 5 to 50 μm, more preferably 10 to 200 μm.

[0044] Detection method:

[0045] S1. Number of oligomer contaminations: After placing the surface protective film in a dryer at 140°C for 10 minutes, the surface was photographed using a high-speed scanning electron microscope, i.e., a high-speed scanning electron microscope HEM6000 produced by Guoyi Quantum Technology Co., Ltd., at 2000 times magnification, 5 random positions were photographed to find the number of oligomer contaminations with a diameter of 0.5 μm or more in the maximum length direction in a square area of ​​40 μm on one side in the central part;

[0046] S2. The surface protection film is directly adhered to the stainless steel plate which has been cleaned by normal adhesion with a rubber roller, i.e., light load, and then a 2kg rubber roller is passed back and forth once to make it fit tightly, and it is directly placed under the conditions of temperature 23°C and humidity 55±5%RH for 1 day, and then cut into strips with a width of 25mm, which are installed in a tensile testing machine, and the stainless steel plate is fixed, and the laminated film is stretched at 180° at a speed of 300mm / min, and its strength is taken as the normal adhesion;

[0047] S3. Normal adhesion and its rate of change after being placed at 60°C for 1 week after application. The sample prepared in the same manner as the above normal adhesion was placed at 60°C for 1 week, returned to room temperature, and the adhesion after 30 minutes was measured using a tensile testing machine. The normal adhesion after 1 week was taken as the value, and the value obtained by dividing the adhesion in this state by the value of the normal adhesion was taken as the rate of change;

[0048] S4. Based on the German RHEOTEST falling ball viscometer, the adhesive layer of the surface protection film is installed on the falling ball adhesion measuring instrument for measurement. At this time, the maximum ball size that stops on the adhesive layer is taken as the viscosity value, and the inclination angle is 30°;

[0049] S5, light transmittance / Hertz light transmittance: The transmittance was measured at a wavelength of 550nm, using a BYK-4775 transmission haze meter produced by BYK of Germany;

[0050] S6. Number of foreign bodies in polyester film: Cut the polyester film into 210 mm long x 148 mm wide, i.e., an area of ​​310.8 cm 2 , the entire range of the film is inspected for foreign matter by visual inspection using the cross Nicol method, and then the foreign matter detected in the sample film is observed by transmitted light using an optical microscope, and the maximum diameter of the portion observed as the optical abnormal range is taken as the size of the foreign matter. In addition, when the voids existing around the foreign matter particles are observed in the optical abnormal range, the size of the foreign matter particles is included. Then, the size of the foreign matter particles is divided into those with an average diameter of more than 5um, less than 25um, and an average diameter of more than 25um, and the foreign matter particles are counted and obtained;

[0051] S7. Number of surface defects: The obtained surface protection film was pasted on the polarizing plate and cut into pieces with a length of 210 mm and a width of 148 mm, i.e., an area of ​​3310.8 cm2 , using its reflected light under fluorescent light, calculate the level of surface unevenness that can be visually confirmed;

[0052] S8. Surface resistance: The surface resistance is measured using a resistance measuring instrument manufactured by Takeda Rikensha at a temperature of 23°C and a humidity of 65% RH. The surface resistance is measured after a voltage of 100 V is applied for 1 minute. The surface resistance is measured when an antistatic layer is provided on a polyester film. The surface resistance is less than 1×10 to the 13th power Ω / □.

[0053] Example 1

[0054] As a polyethylene terephthalate film, a polyethylene terephthalate polymer containing 0.1% by weight of true spherical silica particles with an average particle size of 0.15 μm and an intrinsic viscosity of 0.62 was melted in an extruder, and was closely adhered to a rotating cooling drum maintained at 40° C. from a die by an electrostatic bonding method, and was rapidly cooled to form an unstretched film. Subsequently, the unstretched film was longitudinally stretched 3.5 times, further transversely stretched 3.6 times, and then heat-fixed at 220° C. to obtain a biaxially oriented polyethylene terephthalate film with a thickness of 5 μm. As the coating of the antistatic layer, the 4th-level ammonium salt type cationic polymer compound, i.e., M550-1 produced by Guangzhou Anpin Chemical Co., Ltd., with a solid content of 30%, 50% by weight, and the epoxy resin curing agent, i.e., epoxy curing agent fast curing 103R, with a solid content of 7%, 50% by weight, produced by Guangzhou Yike New Material Technology Co., Ltd., are mixed, diluted to 5% by weight with a mixed solvent, i.e., water / isopropanol = 1 / 1, to adjust the antistatic agent coating liquid. The front side of the biaxially oriented polyethylene terephthalate film is subjected to corona treatment, and the coating liquid is applied to the opposite side using a gravity coater, and the coating film is dried and hardened at 150°C for 1 minute, and an antistatic layer with a thickness of 0.3μm is set to obtain an antistatic film. Next, as an antifouling liquid, 100% by weight of a mixture of polyethyleneimine octadecyl carbamate, RP-20 produced by Hubei Tuobang Chemical Co., Ltd., 10% by weight, i.e., solid weight, polyester resin, 1510 produced by Jining Huakai Resin Co., Ltd., 65% by weight, i.e., solid weight, and melamine resin, NK-12 produced by Henan Binhai Industrial Co., Ltd., 25% by weight, i.e., solid weight, was added to obtain an antifouling coating liquid of 50% by weight % in isopropanol solution of 5% by weight of p-toluenesulfonic acid. The antifouling coating liquid was applied to the antistatic layer of the previous antistatic film using a gravity coater, and the coating was dried and hardened at a temperature of 150° C. for 30 seconds to form an antifouling layer with a thickness of 0.3 μm. As an acrylic adhesive, the main monomer is 2-ethylhexyl acrylate, the comonomer is vinyl acetate, and the functional group-containing monomer is hydroxyethyl methacrylate. In a ratio of 7:2:1, azobisisobutyronitrile is used as a reaction catalyst in a solvent of ethyl acetate to carry out solution polymerization, and a polymer for an adhesive layer with a weight average molecular weight of about 450,000 is prepared. In addition, except for the thickness of the release paper, a coating liquid prepared according to the following method is applied to one side of a biaxially oriented polyethylene terephthalate film with a thickness of 38um prepared in the same manner as above, and a coating amount of 6g / ㎡, i.e., wet, is applied, and heated at a temperature of 140°C for drying and hardening for 1 minute to prepare a release film with a release layer thickness of 0.1um.The silicone coating liquid is prepared by dissolving a reactive curing silicone composed of vinyl polydimethylsiloxane and dimethylhydrogensilane in a toluene solvent to prepare a solution with a solid content concentration of 2%, and adding a platinum catalyst to the solution. The evaluation results of the surface protective film are as follows. Figure 1 shown.

[0055] Example 2

[0056] The surface protection film was prepared in the same manner as in Example 1, except that a conductive coating in which tin-antimony conductive fillers are dispersed in a polyester resin, namely SRK-2024 produced by Qingdao Jundun New Materials Co., Ltd., was used instead of the antistatic coating liquid composed of a quaternary ammonium salt type cationic polymer compound and an epoxy resin curing agent. The evaluation results of the surface protection film are shown in FIG. Figure 1 shown.

[0057] Comparative Example 1

[0058] As the antifouling liquid, a surface protective film was prepared in the same manner as in Examples 1 and 2 except that a 100% by weight portion of a mixture of polyethyleneimine octadecyl carbamate, i.e., RP-20, produced by Hubei Tuobang Chemical Co., Ltd., 30% by weight, i.e., solid weight portion, a polyester resin, i.e., 1510, produced by Jining Huakai Resin Co., Ltd., 55% by weight, i.e., solid weight portion, and a melamine resin, i.e., NK-12, produced by Sanhe Nan Binhai Industrial Co., Ltd., 15% by weight, i.e., solid weight portion, was used, and a 50% by weight isopropanol solution of p-toluenesulfonic acid was added. The properties of the laminated film are shown in FIG. Figure 1 shown.

[0059] Comparative Example 2

[0060] Except that the thickness of the anti-pollution layer is 0.01 μm, the other preparation methods are the same as those in Comparative Example 1. The evaluation results of the surface protection film are as follows: Figure 1 shown.

[0061] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A display surface protective film with antifouling and antistatic functions, comprising a polyester film, characterized in that: The centerline average roughness of the polyester film, i.e., Ra, is preferably 2-500 nm. For the area of ​​the side 210 mm and the side 148 mm directly therefrom on the polyester film, the number of foreign matters with an average diameter of 25 μm or more is preferably 0, and the number of foreign matters with an average diameter of 5 μm or more and less than 25 μm is preferably 10 or less. The surface protection film uses an antistatic film as a substrate, and the antistatic film is provided with a layer containing an antistatic agent on at least one surface of the polyester film. As an adhesive, a thermoplastic resin of a thermoplastic polyester resin and an acrylic resin is used. An antifouling layer is provided on one surface of the antistatic film. The antifouling layer adopts a formulation of an adhesive and an antifouling agent, and the antifouling agent accounts for 3 to 25% by weight of the antifouling layer. As the antifouling agent, an alkyl polymer-based release agent with particularly low migration is preferred from the perspective of preventing contamination during the process. As an adhesive, an adhesive using a thermosetting resin as the antifouling layer is used. The polyester film protective film includes an adhesive layer on the antistatic film, the adhesive layer is provided on the surface opposite to the surface provided with the antifouling layer, and the antifouling layer and the adhesive layer are located between the antifouling layer and the antifouling layer. The opposite side of the antistatic film; an adhesive layer is set to paste and fix the surface protection to the relative substrate, the adhesive layer is made of an adhesive, which is an acrylic adhesive; the thickness of the adhesive layer is 5 to 50um, the normal adhesion of the adhesive layer to the stainless steel plate is 3g / 25mm~50g / 25mm, the adhesive layer should be adhered to the stainless steel plate, 60℃, and the normal adhesion change rate is preferably 0.5~2.0 times before and after one week. The adhesive can be applied directly to the film or on the release paper once, and after it is dried, the antistatic The films are pasted together to transfer the adhesive, coated once on a release paper with a smooth surface, and transferred to the antistatic film. The drying temperature and time are set at a temperature of 50 to 150°C for 10 seconds to 5 minutes. The surface protective film has a light transmittance of 70% and a haze of 10%. The release paper adopts a laminate structure in which the release paper is arranged on the adhesive layer to protect the adhesive layer of the surface protective film, and a release paper with a polyester film as a base material is further laminated on the adhesive layer of the surface protective film.

2. The display surface protective film with antifouling and antistatic functions according to claim 1, characterized in that: The antistatic layer is mixed with a crosslinking agent, and the crosslinking material adopts hydroxymethylated and alkylated melamine compounds, urea compounds, acrylamide compounds, epoxy compounds, and polyisocyanate compounds.

3. The display surface protective film with antifouling and antistatic functions according to claim 1, characterized in that: The antistatic agent adopts surfactant type antistatic agent, cationic antistatic agent with cationic substituent group, including quaternary ammonium salt, pyridinium salt, 1-3 amino group, anionic antistatic agent with anionic substituent group, including sulfonic acid base, nitrate base, phosphate base, and amino acid and aminosulfate amphoteric antistatic agent, amino alcohol, glycerol and polyethylene glycol nonionic antistatic agent, used as monomer and high molecular polymer, conductive polymer, including polyaniline, polypyrrole, polythiophene, tin and antimony filler, when setting polyester film, setting antistatic layer before completing crystal orientation during film formation, in order to set antistatic layer, antistatic agent and adhesive are coated on polyester film, and coating method adopts roller coating method, gravure coating method, reverse coating method, spray coating method; They can be used alone or in combination.

4. The display surface protection film with antifouling and antistatic functions according to claim 1, characterized in that: The thickness of the antifouling layer is 0.05 to 0.8um. ​​When the antifouling layer is thinner than 0.02um, it cannot prevent the precipitation of oligomers. When it is thicker than 3um, it is easy to cause blockage. When the antistatic film is set, the antifouling layer is set before the crystal orientation is completed during film formation. In order to set the antifouling layer, the antifouling agent and adhesive are usually coated on the antistatic film. The coating method adopts roller coating, gravure coating, reverse coating, and spraying. They can be used alone or in combination.

5. The display surface protective film with antifouling and antistatic functions according to claim 1, characterized in that: The adhesion of the adhesive, the size of the ball in the ball adhesion measurement is preferably 2 / 32 to 10 / 32 inches. After the surface protection film is pasted to the other substrate, it needs to be peeled off in the next manufacturing assembly process and the last process. The center line average roughness of the adhesive layer, i.e. Ra, is preferably 2 to 500nm. The center line average roughness of the adhesive layer is measured by scanning the surface of the laminated film using a non-contact three-dimensional surface roughness meter to measure the displacement of the film surface. The center surface average roughness, i.e. Ra, is obtained through surface analysis software. The acrylic adhesive used is preferably the following adhesive.

6. The display surface protection film with antifouling and antistatic functions according to claim 1, characterized in that: As the base material of the release paper, a polyester film is used. The polyester film has the same structure as the polyester film of the surface protection film. The polyester film of the release paper is preferably a biaxially stretched polyester film. Preferably, a release layer is formed on one surface of the release paper.

7. The display surface protection film with antifouling and antistatic functions according to claim 6, characterized in that: The components forming the release paper are mixed with various well-known additives, including ultraviolet absorber pigments, defoaming agents, and antistatic agents. The release layer is applied by applying a coating liquid containing the components forming the separation layer onto a base film and heating and drying to form a coating film. The heating conditions are 20-60 seconds at 120-150°C, and the coating methods include a roll coater method and a comma coater method.

8. The display surface protection film with antifouling and antistatic functions according to claim 1, characterized in that: An adhesive layer is provided between the base film and the release layer, and as a component forming the adhesive layer, when the release layer is a silicone resin layer, a silane coupling agent is preferred.

9. The display surface protection film with antifouling and antistatic functions according to claim 8, characterized in that: The silane coupling agent is more preferably represented by the general formula Y-Si-X 3, where Y represents a functional group represented by amino, epoxy, vinyl, methacrylate, or mercapto, and X represents a hydrolyzable functional group represented by alkoxy. The thickness of the adhesive layer is in the range of 0.02 to 2 μm.

10. A method for preparing a display surface protective film with antifouling and antistatic functions, based on the display surface protective film with antifouling and antistatic functions according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1, an antistatic layer is provided on the polyester film. On the antistatic film, an anti-seepage layer and an adhesive layer are provided as a surface protective film, in which the non-polluting anti-slip layer and the adhesive layer are located on the opposite side of the antistatic film. After the surface protective film is placed at 140° C. for 10 minutes, the surface of the anti-fouling layer satisfies the following conditions: Step S2, in a square area with a side of 40 μm, the surface protection film is an antistatic film in which an antistatic layer is arranged on a polyester film, and an antifouling layer and an adhesive layer are arranged on the pipe. In the antistatic film, the antistatic layer is arranged on one side of the polyester film, and can also be arranged on both sides; Step S3, the antifouling layer and the adhesive layer are located on the opposite side of the clamped antistatic film, the surface protective film, for the surface of the antifouling layer after being placed at 140°C for 10 minutes, in the square area with a side of 40μm, there are only five low-sided contamination levels with a diameter of 0.5μm or more in the maximum length direction. If more than 5 exist, the surface of the metal roller in the process, the polyester film is used as the substrate of the antistatic film of the surface protective film substrate, and the use of the polyester film can be manufactured by the existing known manufacturing method, preferably the biaxially oriented polyester film is the first choice, as the biaxially oriented polyester film , biaxially oriented polyethylene terephthalate films and biaxially oriented polyethylene-2,6-phthalate films can be used, and these films can be single-layer films or multi-layer films in their structure. In the case of multi-layer films, a multi-layer structure with any number of layers can be formed by coextrusion. The polyester constituting the polyester film is preferably a crystalline linear saturated polyester composed of an aromatic dibasic acid component and a diol component, including polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate and polyethylene-2,6-naphthalene dicarboxylate; Step S4, in addition, a part of which is a copolymer substituted by other components, can also be a mixture with polyalkylene glycol or other resins; when the biaxially oriented polyester film is used as the polyester film, the biaxially oriented polyester film can be manufactured by methods such as sequential biaxial stretching method and simultaneous biaxial stretching method; Step S5, when the sequential biaxial stretching method is adopted, the following method is adopted: after the polyester polymer is fully dried, it is extruded from the tube core, including the T-tube core and the I-tube core, onto a cooling drum by melt extrusion, and quenched to obtain an unstretched film and a co-extruded unstretched film, and then the unstretched film is longitudinally stretched 2 to 5 times at a temperature of 60 to 140° C., and then transversely stretched 2 to 5 times at a temperature of 80 to 150° C., and then heat-fixed at a temperature of 160 to 260° C. for 1 to 100 seconds, and the heat-fixing treatment is performed under the condition of limiting shrinkage; Step S6. During melt extrusion, an electrostatic bonding method is used. In addition, in order to avoid breakage in a specific direction, the isotropy of the biaxially oriented polyester film is preferably as high as possible, including the above-mentioned longitudinal and transverse stretching ratios are preferably the same, and the thickness of the film is preferably 5 to 50 μm, more preferably 10 to 200 μm.